Experimental models of sepsis and septic shock: an overview - Garrido,Alejandra G. (2004)
Sepsis remains a major cause of morbidity and mortality in surgical patients and trauma victims, mainly due to sepsis-induced multiple organ dysfunction. In contrast to preclinical studies, most clinical trials of promising new treatment strategies for sepsis have fails to demonstrate efficacy. Although many reasons could account for this discrepancy, the misinterpretation of preclinical data obtained from experimental studies, and especially the use of animal models that do not adequately mimic human sepsis may have been contributing factors. In this review, the benefits and limitations of various animal models of sepsis are discussed to clarify the extend to which findings are relevant to human sepsis, particularly with respect to the subsequent design and execution of clinical trials. Such models include intravascular infusion of endotoxin or live bacteria, bacterial peritonitis, cecal ligation and perforation, soft tissue infection, pneumonia or meningitis models, using different animal species including rats, mice, rabbits, dogs, pigs, sheep and nonhuman primates. Despite several limitations, animal models remain essential in the development of all new therapies for sepsis and septic shock, because they provide fundamental information about the pharmacokinetics, toxicity, and mechanism of drug action that cannot be duplicated by other methods. New therapeutic agents should be studies in infection models, even after the initiation of the septic process. Furthermore, debility conditions need to be reproduced to avoid the exclusive use of healthy animals, which often do not represent the human septic patient.